Mixotrophic algal-protein production and techno-economic analysis based in medium formulation (Research, Society and Development, 2021)
The use of Spirulina platensis for human consumption, due to the wide benefits gained as higher protein content, low calories, and high nutritional value, grows every year. Besides, several studies have tested alternative culture media to increase the level of biomass density and protein content, besides reducing the costs of production. Glucose (GLC) is a known component used to provide cell growth because it increases the carbon content of microalgae; however, there is no record of the use of the fetal bovine serum (FBS), a supplement widely used for animal cell culture. The current work aimed to analyze the isolated and combined effect of glucose and FBS, synergism, and antagonism on the S. platensis culture development. A techno-economic analysis was also proposed. The effect between GLC and FBS increased the biomass density (0.44g/L) and chlorophyll content (0.72mg/m3). However, the condition with higher protein concentration seemed to be the one supplemented only with FBS. The result may show that protein production does not follow the same rule as biomass density. Further, the cost-benefit analysis showed gains of a projected venture with the discounted payback period (DPBP) of three years.